2009
DOI: 10.1080/10790268.2009.11754561
|View full text |Cite
|
Sign up to set email alerts
|

Therapists' Roles in Pressure Ulcer Management in Persons With Spinal Cord Injury

Abstract: Background: Among veterans with spinal cord injury (SCI), severe pressure ulcers (PrU) are treated by interdisciplinary rehabilitation teams in SCI units. Method: Cross-sectional survey administered to therapists attending a conference of the Therapy Leadership Council in SCI. Participants: Respondents included physical therapists (PTs; n 5 24) and occupational therapists (OTs; n 5 15). Main Outcome Measurements: Wound care practices as indicated by 75% or more of participants as ''usual practice.'' Results: I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 19 publications
3
14
1
Order By: Relevance
“…A small percentage (38%) of the study sample reported being involved in direct wound care management. This differs to Guihan et al (2009)'s findings where they reported more than 75% of the physiotherapists to be involved in direct wound care. Eighteen percent of the respondents from this study used electrotherapy to manage pressure sores and the modalities most commonly used were ultrasound and laser.…”
Section: Use Of Protocols and Involvement In The Treatment Of Patientcontrasting
confidence: 99%
See 2 more Smart Citations
“…A small percentage (38%) of the study sample reported being involved in direct wound care management. This differs to Guihan et al (2009)'s findings where they reported more than 75% of the physiotherapists to be involved in direct wound care. Eighteen percent of the respondents from this study used electrotherapy to manage pressure sores and the modalities most commonly used were ultrasound and laser.…”
Section: Use Of Protocols and Involvement In The Treatment Of Patientcontrasting
confidence: 99%
“…Interventions that were carried out by 70% or more of the physiotherapists were taken to represent "common practice", which is fairly similar to the benchmark of 75 % which was set as usual practice in Guihan et al (2009)'s study. Seventy percent of the physiotherapists indicated carrying out the following interventions when the patient was in bed: upper limb muscle strengthening, lower limb passive movements, positioning into prone and side lying as well as upper limb passive movements and passive stretching.…”
Section: Physiotherapy Interventions For the Paraplegic Patient With mentioning
confidence: 99%
See 1 more Smart Citation
“…The reliability of the SCIPUS and Braden scales for the prediction of SCI risk has been demonstrated; however, their validity has not been reported. 12 The interview questionnaire included questions on sociodemographic status and lifestyle factors, the latter were selected based on previous studies and our clinical experience [5][6][7][8]10,13 and are shown in Table 1. On-thewheelchair IP measurements of both groups were done using the FSA (Force sensing Array) Pressure Mapping System (Vista Medical Ltd, Manitoba, Canada); peak pressure, contact area and average pressure were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…7 In the clinical setting, we contribute to PU prevention by providing pressure redistribution on the wheelchair, instructing patients in pressure relief practices and evaluating activities that include the risk of PUs. 8 Therefore, knowing which aspects of daily living strongly influence the risk of PU occurrence would help guide prevention strategies. Characterization of the relationship between interface pressure (IP) measurements on the wheelchair and PUs is also essential, 9 as IP may be useful for the investigating seat pressure and daily living-related risk factors for PUs in patients with SCI.…”
Section: Introductionmentioning
confidence: 99%